Academic Skills for Interdisciplinary Studies - Buis, Joris J. W.; Visser, Vincent R.; Post, Ger (Book collections on Project MUSE., 2016)
Academic skills are the tools that enable you to gain, develop and critically discuss new knowledge during and after your Bachelor's and Master's programme. This handbook offers practical instructions, tips, and tricks that help undergraduate students to develop the skills needed for an interdisciplinary curriculum. The book focuses on the following elements: How to study effectively, reading scientific literature, collecting and assessing literature for your research, argumentation, academic writing, presentation skills, scientific interviews, debating, reflection, critical thinking.